Different Structural Modification Methods of the Patch for Reducing the Size of An Microstrip Patch Antenna - Ferdous, Nayla; Chin Hock, Goh; Hamidah A. Hamid, Saidatul; Nazri Abdul Raman, Mohamad; Sieh Kiong, Tiong; Ismail, Mahamod (International Journal of Engineering and Technology, 2018)
The aim of this paper is to present a simulation and analysis of a rectangular microstrip patch antenna with three different structural modifications to reduce the size of the antenna. We have tried to decrease the size of the antenna by inducing three different shaped slits inside the patch of the antenna. All these models have been designed and analyzed using CST Microwave Studio software. For designing the antennas, Flame Retardant 4 (FR-4 lossy) has been used as the substrate material with a dielectric constant of Ôr=4.3. The antenna works at the frequency of 2.4 GHz. Performance characteristics such as return loss S11 parameter<-10 dB, directivity, side lobe level, gain and bandwidth of each of the modified designs are obtained and compared with the original design. We were able to reduce the size by maximum 18% and minimum 7% by only inducing the slits, while maintain the performance.Â